Among cosmopolitan values and strategic interests: Liberal and realist discourses of Canada’s international security policy during post-cold war (2014)
summary The purpose of the article is to explain the liberal and realist discourses that underpinned the Canadian International Security Policy (CISP) during the post-Cold War. In particular, it offers evidence to show that Canadian governments inevitably debate between cosmopolitan values and strategic interests in formulating their respective policies of international security. After considering how liberal and realist orientations of this policy have been studied in the literature on CISP, it explains the specific liberal and realist discourses that have shaped international security policies of the governments of Jean Chrétien (1993-2003), Paul Martin (2003-2006) and Stephen Harper (2006 -). As a final consideration, it intends to elucidate the progressive way in which the various Canadian governments have been adopting the United States’ cosmopolitan values and interests regarding international security. © 2014 Universidad Nacional de Colombia. All rights reserved.